2012
DOI: 10.1021/ol300717e
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Synthesis of Chiral Allenes by Sequential Creation of Stereogenic Center and Chirality Transfer in a Single Pot Operation

Abstract: Chiral allenes are readily accessed in a single pot operation in the reaction of terminal alkynes, aldehydes, chiral secondary amines, and zinc halides in good yields (up to 77% yield) and excellent enantioselectivities (up to 99% ee) in toluene at 120 °C. The reaction proceeds through initial formation of chiral propargylamine intermediates with creation of a new stereogenic center and subsequent chirality transfer via an intramolecular hydride shift to produce chiral allenes with high enantiomeric purities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…13 C NMR (125 MHz, CDCl 3 ): δ = 204.0, 135.2, 128.5, 126.6, 126.4, 101.0, 95.4, 37.6, 33.2, 33.1, 26.1, 26.0 ppm. The 13 C NMR spectroscopic data was in agreement with the reported data, see ref 6. IR (KBr): $\tilde {\nu}$ = 3061, 3028, 1936, 1597, 1493, 1450, 758 cm –1 .…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…13 C NMR (125 MHz, CDCl 3 ): δ = 204.0, 135.2, 128.5, 126.6, 126.4, 101.0, 95.4, 37.6, 33.2, 33.1, 26.1, 26.0 ppm. The 13 C NMR spectroscopic data was in agreement with the reported data, see ref 6. IR (KBr): $\tilde {\nu}$ = 3061, 3028, 1936, 1597, 1493, 1450, 758 cm –1 .…”
Section: Methodssupporting
confidence: 89%
“…Although the preparation of a monosubstituted allene from CuBr, a 1‐alkyne, and formaldehyde was reported by Crabbe in 1979, the synthesis of racemic 1,3‐disubstituted allenes from terminal alkynes, aldehydes, morpholine, and ZnX 2 was reported only very recently 5. We have recently reported that zinc halides promote the one‐pot enantioselective synthesis of chiral allenes using aldehydes, terminal alkynes, and the chiral amine derivatives ( 1 – 3 ; Scheme ) 6…”
Section: Introductionmentioning
confidence: 99%
“…The selectivity realized in the formation of chiral propargylamines (87:13 to 99:1 dr) and their conversion to corresponding chiral allenes (75‐86 % ee ) from chiral cis ‐2,3‐diphenylpiperazine derivatives 8 are somewhat lower compared to that realized using chiral trans ‐2,3‐diphenylpiperazine derivatives 5 a . However, such results are not surprising, since the phenyl groups are cis to each other here and hence may adopt a conformation different from the chair conformation of the trans ‐1,2‐diphenyl derivatives, similar to that reported for cis ‐1,2‐di‐ tert ‐butylcyclohexane derivatives .…”
Section: Resultsmentioning
confidence: 79%
“…However, selectivity for conversion to chiral allenes would be lower as the steric crowding of the phenyl group in the propargylamines 20 ca–cd and 21 ca–cd would make it more difficult to go through the transition state 27 involving coordination of zinc bromide with phenylethynyl moiety and the N ‐benzyl nitrogen of the propargylamine. It is of interest to note that the propargylamine prepared using the chiral 2‐phenyl pyrrolidine 5 b which does not have another coordinating nitrogen group gave chiral allenes with only 66–78 % ee …”
Section: Resultsmentioning
confidence: 99%
“…Recently, we developed a “chiral amine approach” for highly enantioselective synthesis of chiral allenes by using terminal alkynes, aldehydes, and chiral amines promoted by zinc halides in a single‐pot operation 10a. Thus, the zinc halide promoted reaction of chiral secondary amines 1 – 4a , 1‐decyne 5a , and benzaldehyde 6a at 120 °C (Scheme ) has been developed to access the chiral allenes in very high enantioselectivity up to 99 % ee .…”
Section: Introductionmentioning
confidence: 99%